The infuence of production systems in postponement make-to-stock compagny in the graphic industry - Rodrigues, Paulo Cesar Chagas [UNESP]; Marins, Fernando Augusto Silva [UNESP]; De Souza, Fernando Bernardi [UNESP] (My University, 2011)
The supply chain management, postponement and demand management operations are of strategic importance to the economic success of organizations because they directly influence the production process. The aim of this paper is to analyze the influence of the postponement in an enterprise production system with make-to-stock and with seasonal demand. The research method used was a case study, the instruments of data collection were semi-structured interviews, document analysis and site visits. The research is based on the following issues: Demand Management which can be understood as a practice that allows you to manage and coordinate the supply chain in reverse, in which consumers trigger actions for the delivery of products. The Supply Chain Management is able to allow the addition of value, exceeding the expectations of consumers, developing a relationship with suppliers and customer's win-win. The Postponement strategy must fit the characteristics of markets that require variety of customized products and services, lower cost and higher quality, aiming to support decision making. The production system make-to-stock shows enough interest to organizations that are operating in markets with high demand variability. © 2011 IEEE.
Keywords: Demand Management; make-to-stock; Postponement; Supply Chain Management (SCM); Customized products; Data collection; Document analysis; Economic success; Enterprise production; Graphic industry; High demand; Infuence; Lower cost; Make-to-stock; Postponement strategies; Production process; Production system; Relationship with suppliers; research methods; Seasonal demands; Semi structured interviews; Site visits; Win-win; Decision making; Logistics; Research; Supply chain management